2017
DOI: 10.1002/ana.25035
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol improves cerebellar learning deficit in myoclonus–dystonia: A clinical and electrophysiological investigation

Abstract: The combination of findings of reduced baseline acquisition of conditioned eyeblink responses and normal blink reflex recovery cycle in patients who improved significantly with alcohol intake suggests a crucial role of cerebellar networks in the generation of symptoms in these patients. Ann Neurol 2017;82:543-553.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
38
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 43 publications
(44 citation statements)
references
References 47 publications
3
38
0
3
Order By: Relevance
“…16,17 In addition, the partial alleviation of symptoms of DYT11 with alcohol, to which the cerebellum is highly sensitive, is often taken as a clinical marker of potential cerebellar involvement. 8,17 The causative mutation of DYT11 dystonia, ϵ-sarcoglycan, is expressed in multiple nonneural and neural regions throughout development. 18 Importantly, brain-specific isoforms demonstrate high expression in the Purkinje cells and neurones of the dentate nucleus, 8 in motor learning on a beam-walking test have been observed in a Purkinje cell-specific conditional knockout for ϵ-sarcoglycan.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…16,17 In addition, the partial alleviation of symptoms of DYT11 with alcohol, to which the cerebellum is highly sensitive, is often taken as a clinical marker of potential cerebellar involvement. 8,17 The causative mutation of DYT11 dystonia, ϵ-sarcoglycan, is expressed in multiple nonneural and neural regions throughout development. 18 Importantly, brain-specific isoforms demonstrate high expression in the Purkinje cells and neurones of the dentate nucleus, 8 in motor learning on a beam-walking test have been observed in a Purkinje cell-specific conditional knockout for ϵ-sarcoglycan.…”
Section: Discussionmentioning
confidence: 99%
“…6 In humans with DYT11 dystonia, imaging studies have revealed metabolic changes in the cerebellum (in conjunction with other regional abnormalities) 7 and impaired saccadic adaptation has been taken as one of the first functional markers of cerebellar dysfunction in the disease. 9 Results with another associative cerebellar learning paradigm, eye blink conditioning, have to date been mixed (one study showing normal acquisition, 4 the other impaired acquisition) 17 . Whether the subclinical deficit in saccadic adaption was indicative of a more general deficit in adaptation was the core experimental question explored in this paper.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that dysfunction of the striato‐pallido‐thalamo‐cortical network is critically involved in the generation of this motor phenotype . Metabolic neuroimaging and various neurophysiological studies point to a dysfunctional cerebello‐thalamo‐cortical pathway . Similar to other dystonic syndromes, abnormal sensorimotor integration with hypoactivity within the premotor, sensory, and parietal cortices and the cerebellum has been shown in DYT‐ SGCE .…”
mentioning
confidence: 90%
“…© 2018 International Parkinson and Movement Disorder Society crucial role of the cerebellothalamic pathways in the generation of these motor symptoms, as well as objective improvement after alcohol intake. 6 The disease typically starts with action myoclonus, which is, in fact, the most disabling manifestation based on our clinical experience, and is followed by focal or segmental dystonia of the upper body. The clinical picture also includes a broad spectrum of neuropsychiatric symptoms, mostly anxiety-related disorders and obsessive-compulsive disorder, and an increased risk of alcoholism.…”
mentioning
confidence: 95%
“…The brain‐specific function of the gene is not completely elucidated, but it is a part of the dystrophin‐associated membrane complex . Histopathological, neurophysiological, and imaging studies point to a crucial role of the cerebellothalamic pathways in the generation of these motor symptoms, as well as objective improvement after alcohol intake …”
mentioning
confidence: 99%